Strategies utilised by an interpreter at alexandra hospital to enhance communication and eliminate communication barriers - Hlungwani, Nyiko Cynthia (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.